KONTRIBUSI PENDIDIKAN AGAMA ISLAM DAN KONSELING KELUARGA DALAM MENINGKATKAN KETAHANAN KELUARGA DI MASA PANDEMI COVID-19 - Hunainah, Hunainah; Mujib, Abdul; Riswanto, Dodi (QATHRUNÂ, 2024)
The aim of this research is to determine the contribution of Islamic religious education and family counseling to increasing family resilience in aspects of spirituality during the Covid-19 pandemic. The focus of this research is to change the paradigm of married couples to be more positive by carrying out lots of worship activities at home. The method used is a qualitative approach with data collection techniques, namely observation, documentation studies and audio-visual information. The conclusions of this research are as follows: 1) married couples must have good communication patterns; 2) conceptualization of sharia-based family education as an effort to increase family resilience; 3) increase motivation in the family; 4) strategies for instilling maqasid sharia values in family functioning during the pandemic; 5) family counseling intervention strategies